Photo-Irradiated Biosynthesis of Silver Nanoparticles Using Edible Mushroom Pleurotus florida and Their Antibacterial Activity Studies - Ravishankar Bhat; Raghunandan Deshpande; Sharanabasava V. Ganachari; Do Sung Huh; A. Venkataraman (Bioinorganic Chemistry and Applications)
This is a report on photo-irradiated extracellular synthesis of silver nanoparticles using the aqueous extract of edible oyster mushroom (Pleurotus florida) as a reducing agent. The appearance, size, and shape of the silver nanoparticles are understood by UV-visible spectroscopy, field emission scanning electron microscopy, transmission electron microscopy, and atomic force microscopy. The X-ray diffraction studies, energy dispersive X-ray analysis indicate that particles are crystalline in nature. Fourier transform infrared spectroscopy analysis revealed that the nanoparticles are covered with biomoieties on their surface. As can be seen from our studies, the biofunctionalized silver nanoparticles thus produced have shown admirable antimicrobial effects, and the synthetic procedure involved is eco-friendly and simple, and hence high range production of the same can be considered for using them in many pharmaceutical applications.